통일형 벼에서 메소트리온계 제초제 저항성 연관 DNA marker 탐색 - 이지윤(Ji-Yoon Lee); 조준현(Jun-Hyeon Cho); 이종희(Jong-Hee Lee); 조수민(Su-Min Cho); 권영호(Young-Ho Kwon); 박동수(Dong-Soo Park); 송유천(You-Chun Song); 고종민(Jong-Min Ko) (Korean journal of breeding, 2018)
This study was conducted to identify DNA markers related to resistance to herbicide containing mesotrione in Tongil type rice. Two Tongil type elite lines; Milyang154 and Suweon382, showed resistance to mesotrione, whereas the others were susceptible at 20 days after mesotrione application, and severe growth inhibition was observed in the remaining 13 lines. As a result of analysis of mesotrione resistance using 190 F2 populations derived from a cross of Hanareum2 (susceptible) and Milyang154 (resistant), the mesotrione resistance locus was shown to be a single dominant gene with a 3:1 segregation ratio (X2=1.19, P=0.31). To identify a DNA marker closely linked to the mesotrione resistance gene, bulked segregant analysis (BSA) was adopted. The DNA marker RM3501 was identified on chromosome 2 with a recombinant value of 0.53 to the mesotrione resistance gene. Mst1(t) was located between SSR (simple sequence repeat) markers RM3501 and RM324 with a physical map distance of 10.2 Mb–11.4 Mb on chromosome 2. The band pattern of agarose gel electrophoresis of the SSR marker RM3501 showed the same segregation pattern with respect to mesotrione treatment in 20 Tongil type varieties and a BC2F2 segregation population derived from a cross between Unkwang (resistant) and Hanareum2 (susceptible). Thus, the RM3501 DNA marker could be used in breeding programs for Marker Assisted Selection in mesotrione resistant rice breeding. KCI Citation Count: 0